The 39 clues : In too deep - Watson, Jude. (New York : Scholastic Ltd, 2012)
Amy and Dan cross the oceans on the trail of a famous aviator, but they find more than they're looking for. Their enemies are becoming more vicious, and the truths they discover more crushing than ever.
Keywords: GAMES -- FICTION